Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.bcmd.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the activity levels of rat FVIII and human FVIII delivered by adeno-associated viral vectors both in vitro and in vivo

Abstract: The development of a novel coagulation factor VIII (FVIII) expression cassette with an enhanced activity for gene therapy of hemophilia A (HA) is essential. The biological properties of several non-human FVIII sequences, such as porcine and canine, have been evaluated. Here, we compared the activity level of rat FVIII (rFVIII) and human FVIII (hFVIII) by using single-chain and dual-chain strategies in 293 T cells and the HA mice. In both in vitro and hydrodynamic injection studies, the activity of rFVIII detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It was reported that cavitation prolongs transgene expression when coupled with hydrodynamic force [178]. Similarly, various nonviral and viral vectors, such as polyplexes [57,62,217], cationic liposomes [135], adenoassociated virus [86,103,[220][221][222][223], lentivirus [38,224,225], and foamy virus [34], have been administered under hydrodynamic conditions to achieve improved gene transfer.…”
Section: Regional Hydrodynamic Deliverymentioning
confidence: 99%
“…It was reported that cavitation prolongs transgene expression when coupled with hydrodynamic force [178]. Similarly, various nonviral and viral vectors, such as polyplexes [57,62,217], cationic liposomes [135], adenoassociated virus [86,103,[220][221][222][223], lentivirus [38,224,225], and foamy virus [34], have been administered under hydrodynamic conditions to achieve improved gene transfer.…”
Section: Regional Hydrodynamic Deliverymentioning
confidence: 99%
“…As the contain the sugar and carbohydrates which cause the fat accumulation in body so the person should avoid sugary drinks and fruit juice to secure from obesity [40].…”
Section: Avoid Sugary Drinks and Fruit Juicementioning
confidence: 99%